IT Outsourcing vs. Smart-sourcing in the Utility Industry - Al Bloushi, Shereena Yousef (2010)
Businesses turn to outsource their information technology activities to third parties for different reasons. This research has been conducted to determine the challenges organizations and companies are encountering because of relying on IT sourcing and finding ways in which the challenges can be addressed. The research was done by relying on a case study concerning a company “X” which is a government utility organization to see how efficiently outsourcing has been done on organization “X”. The organization that was investigated was one of the pioneer firms in United Arab Emirates that started with IT outsourcing. The examination brought along with it limitations for the research, limitations such as political, economic and technological with respect to the utility industry. These limitations indicated that appropriate IT resourcing could raise the assumptions with respect to IT outsourcing. The results of the research have also indicated that significant differences in structuring the IT outsourcing may hinder the success of the IT outsourcing agreement while a successful management and governance may stabilize the relationship, expectations, strategies, visions and operations.